A feature-inheritance approach to scalar-focus object preposing in English, Mandarin Chinese, and Spanish - Yang, Jiahui (Complutense Journal of English Studies, 2024)
This paper discusses the syntax of scalar-focus object preposing, which is found compatible with constituent-adverbs but not with adverbs with a sentential scope. Meanwhile, languages such as English and Mandarin Chinese are found to differ in the position to which the scalar-focus object can be preposed. To account for such cross-linguistic structural differences in a unified way, this paper proposes that such an object carries an interpretable [+Max]-feature and agrees with a functional head to value its uninterpretable discourse-feature, before moving to the specifier position of the latter. Based on the theory of Feature Inheritance, it has been further argued that in English, the functional head in question is C, because the discourse-feature is retained by it, while in Mandarin Chinese this head is T, because it inherits the discourse-feature from C. The potential issue of subject-object ordering in this approach has been delt with by considering the nature of movement and the licensing condition of multiple specifiers. Additionally, the universality of the current proposal has been demonstrated by extending the same approach to Spanish.
Keywords: scalar focus; object preposing; feature inheritance; information structure